What Slice of the Pie? The Corporate Bond Market Boom in Emerging Economies - Diana Ayala; Milan Nedeljkovic; Christian Saborowski (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper studies the determinants of shifts in debt composition among emerging market non-financial corporates. We show that the determinants of bond market access in EMs vary with global cyclical conditions and across local and foreign currency markets. We find that the role for institutions and macro fundamentals in creating an enabling environment for markets increased during the post-crisis period for local currency markets. Foreign bank linkages additionally explain why local currency bond markets increasingly substituted for banks in channeling liquidity to EMs. In the case of foreign currency markets, in turn, global cyclical factors accounted for most of the variation. Furthermore, a country's relative sensitivity to global factors appears to vary with the size of its foreign currency bond market rather than local fundamentals. Our results highlight the risk of capital flow reversal in those EMs that benefited from the upturn in the global financial cycle mostly due to the relative size of their bond markets rather than strong fundamentals.
Keywords: F30; G15; G20; G30; 330; bond markets; capital flows; emerging markets